The Effect of Financial Contents on Social Media Towards Financial Literacy on Generation Z in Sumatra and Java - Angelica, Agnes Enya; Zen, Tuntun Salamatun; Hasanah, Eneng Nur (Journal of Consumer Studies and Applied Marketing, 2023)
Contents with the topics around finances in social media can be utilized to improve financial literacy among Generation Z, considering that Generation Z took the highest proportion compared to other generations in Indonesia and since Generation Z has the highest internet penetration rate and spent the most time on the internet compared to other generations. This research aims to determine the impact of finances on financial literacy in Generation Z, the most significant factor of financial content that affects financial literacy, and to find out which social media and content type is the most impactful. The financial content on social media is measured by the number of social media and content types, the number of creators and topics watched, and duration, while financial literacy is measured by financial attitude, behavior, and knowledge. This research uses quantitative methods, and the data is collected using an online questionnaire. This research gathered 287 samples from Java and Sumatra, Indonesia, and 222 are financial content viewers. The multi-linear regression result found that financial contents affect financial literacy by 20.4%. The total amount of financial topics watched has the most significant impact on financial literacy, while the total amount of social media used to watch financial content has a significant negative impact. The ANOVA result discovered that people who are most often use YouTube to view financial content have the best financial literacy score average.